Investigation of pesticidal ability of humic acid derived from palm oil Empty Fruit Bunch (EFB) vermicompost - Alvyana Khiew Ai May; Rashid Shamsuddin; Lew Jin Hau; Aqsha Aqsha; Nurlidia Mansor; Nur Izzati Mustapa; Murugesu Narasimha (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Humic Acid (HA), a plant’s growth promoter readily available in compost was found to have insect repelling functional groups. This study was conducted to investigate the pesticidal ability of HA extracted from Empty Fruit Bunches (EFB) vermicomposts at Carbon to Nitrogen (C:N) ratio of 25, 30 and 35. Methods The vermicomposts were prepared using EFB, a palm oil mill by-product as the base material with underutilized organic wastes (fishmeal, bonemeal, and bunch ash) as additives to enhance the macronutrients of vermicomposts. Composting was conducted for 52 days with earthworms as composting agents. HA (mass yield of 2.34 – 2.63%) was extracted from the matured vermicomposts through alkaline extraction before acid precipitation.  The insect repelling effectiveness of HA, Garlic Extract (GE) and 87% GE + 13% HA was evaluated by spraying them onto soil samples in different compartments with crickets. Results Vessel with lesser crickets indicates agent sprayed repels insect better. Results showed 87% GE + 13% HA repels insect most effectively, followed by 100% HA and lastly 100% GE. The macronutrients (Nitrogen, Phosphorus and Potassium) were improved upon mixing additive materials to the vermicompost. Conclusion HA alone possesses some ability to repel crickets. It performs better when it is coupled with GE as HA acts as a diluent to promote GE absorption into soil thus enhancing the pesticidal effect. This demonstrates EFB has potential as a precursor material for high value vermicompost with insect repellent ability, thus presenting an opportunity for respective industries to generate value-added products while solving by-product underutilization issue.